2020
DOI: 10.3389/fcell.2020.00670
|View full text |Cite
|
Sign up to set email alerts
|

DDHD1, but Not DDHD2, Suppresses Neurite Outgrowth in SH-SY5Y and PC12 Cells by Regulating Protein Transport From Recycling Endosomes

Abstract: DDHD1 and DDHD2 are both intracellular phospholipases A 1 and hydrolyze phosphatidic acid in vitro . Given that phosphatidic acid participates in neurite outgrowth, we examined whether DDHD1 and DDHD2 regulate neurite outgrowth. Depletion of DDHD1 from SH-SY5Y and PC12 cells caused elongation of neurites, whereas DDHD2 depletion prevented neurite elongation. Rescue experiments demonstrated that the enzymatic activity of DDHD1 is necessary for the prevention of neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Two scientists independently observed homozygous and compound heterozygous mutation in adaptor-related protein complex 4 subunit sigma 1 (SPG52/AP4S1) at 14q21 in Syrian [87] and Caucasian families [88], which induces HSP phenotypes due to defective endosomes trafficking. Maemoto et al [89] showed that DDHD1 protein depletion negatively affects neurite growth due to defective endosomal protein recruitment other than tubular recycling endosome. Another gene, Zinc Finger FYVE-Type Containing 26 (SPG15/ZFYVE26) at 14q24.1, is linked with [90] spatizin, and its mutations lead to HSPs.…”
Section: Chromosome 14mentioning
confidence: 99%
“…Two scientists independently observed homozygous and compound heterozygous mutation in adaptor-related protein complex 4 subunit sigma 1 (SPG52/AP4S1) at 14q21 in Syrian [87] and Caucasian families [88], which induces HSP phenotypes due to defective endosomes trafficking. Maemoto et al [89] showed that DDHD1 protein depletion negatively affects neurite growth due to defective endosomal protein recruitment other than tubular recycling endosome. Another gene, Zinc Finger FYVE-Type Containing 26 (SPG15/ZFYVE26) at 14q24.1, is linked with [90] spatizin, and its mutations lead to HSPs.…”
Section: Chromosome 14mentioning
confidence: 99%